2021
DOI: 10.1111/jch.14188
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and chronic kidney disease in Asian populations

Abstract: This is an open access article under the terms of the Creative Commons Attribution NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…A large number of studies have shown that the degree of portal hypertension is an important prognostic factor for liver dysfunction. , Additionally, necrotizing inflammation of the liver can promote the increase of hepatic vascular tension . At the same time, hypertension is also the main cause of chronic kidney disease . Retrospective analysis showed that the level of serum uric acid was negatively correlated with renal function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have shown that the degree of portal hypertension is an important prognostic factor for liver dysfunction. , Additionally, necrotizing inflammation of the liver can promote the increase of hepatic vascular tension . At the same time, hypertension is also the main cause of chronic kidney disease . Retrospective analysis showed that the level of serum uric acid was negatively correlated with renal function.…”
Section: Introductionmentioning
confidence: 99%
“…10 At the same time, hypertension is also the main cause of chronic kidney disease. 11 Retrospective analysis showed that the level of serum uric acid was negatively correlated with renal function. The level of serum uric acid is directly related to SP and DP.…”
Section: Introductionmentioning
confidence: 99%
“…Forthly, secondary hypertension and dyslipidemia, and genetic familial hypercholesterolemia were not excluded in this study, if any. Finally, the contents of pharmacotherapy for hypertension, which can influence the metabolism of lipids [ 44 , 45 ], the data of renal function and serum uric acid, which contribute to the development of hypertension [ 46 , 47 , 48 , 49 ], and the data of diet were also unavailable in this study. Further studies addressing these limitations are needed to warrant current results.…”
Section: Resultsmentioning
confidence: 99%
“…Among the risk factors for early kidney damage, BP is one of the most important. 20 Indeed, a recent study showed that a higher BP in childhood was correlated with a higher risk of subclinical kidney damage in adults over 30 years of follow‐up. 21 Moreover, short‐term BP variability was independently associated with early kidney abnormalities.…”
Section: Discussionmentioning
confidence: 99%